Bank Indonesia’s role in the electronification of the digital economy as a form of non-military defense - Guntur Eko Saputro; Panji Suwarno; Suwito Suwito; Cakrawati Sudjoko (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
Non-military defense is a defense to deal with non-military threats that can endanger or have implications for national defense. Non-military threats have ideological, political, economic, socio-cultural, technological, public safety, and legislation dimensions. In the general policy of national defense for the years 2020-2024, it is stated that in the policy of implementing non-military defense, it is directed to deal with the dimensions and types of threats by determining the ministry/institution as the main element. Bank Indonesia realizes that the payment system needs to adapt to the presence of digital technology. To that end, BI has issued a blueprint for the Indonesia Payment System (SPI) 2025, one of whose vision is to support the digitization of banking as the main institution in the digital-financial economy, both through open-banking and the use of digital technology and data in the financial business. The research objective is to provide government input on the role of Bank Indonesia in the Electronification of the Digital Economy as a Form of Non-Military Defense. Research with qualitative methods is aimed at understanding social phenomena from the perspective of participants. The results achieved are in accordance with the Role theory that Bank Indonesia encourages banking digitalization, supports the integration of the national digital economy, ensures interlink fintech and banking, to ensure consumer protection and national interests are maintained.